Effectiveness of Dietary Supplement for Skin Moisturizing in Healthy Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Sun, Qian; Wu, Jingping; Qian, Guofei; Cheng, Hongbin (Frontiers in Nutrition, 2022)
Background The dietary supplement industry offers many oral cosmetics that purportedly assist in skin moisturization often with unclear evidence supporting efficacy and safety. To update the accessible proofs pertaining to the safety and effectiveness of oral dietary supplements to facilitate skin moisturizing via an all-around review and meta-analysis. Methods Three on-line databases [Pubmed, Embase, and Cochrane Library (CENTRAL)] were retrieved from January 2000 to November 2021. An overall 66 randomized controlled trials (RCTs) of skin care were recognized. Meta-analysis was performed for dietary supplements with four or more available research. Results Oral collagen or ceramide resulted in a statistically significant increase in skin hydration and a decrease in transepidermal water loss (TEWL) compared to placebo. No benefits regarding the improvement of skin conditions in terms of water content and TEWL were observed for lactic acid bacteria or Lactobacillus fermented foods. A statistically significant and positive effect on skin hydration was observed for both hyaluronan and procyanidin, with an unknown effect on TEWL due to insufficient RCTs. There was a non-significant improvement in the water content of stratum corneum for astaxanthin based on subgroup analyses. Among the dietary supplements trialed in ≤ 3 RCTs, the judgment regarding their effects on skin moisturizing was prevented by inconsistent conclusions as well as insufficient research. All food supplements were safe throughout the research (normally ≤ 24 weeks). Conclusion Oral dietary supplements, including collagen, ceramides, hyaluronan, and procyanidin, were proven to be effective for skin moisturization. At present, for skin moisturization, the proofs supporting the recommendation of other dietary supplements, such as lactic acid bacteria and astaxanthin, are insufficient. Systematic Review Registration http://www.crd.york.ac.uk/PROSPERO/ identifier CRD42021290818